Effect of Lavender Ethanolic Extract on Infarct Volume in Rats Subjected to Ischemia-Reperfusion - Z Rabiei; F Fathi; S Asgharzade; M Rafieian-kopaei (Journal of Medicinal Plants, 2017)
Background: Lavender belongs to the Labiatae family and possesses antioxidant acivity.